Higher BMI predicts liver fibrosis among obese children and adolescents with NAFLD - an interventional pilot study - Hadar Moran-Lev; Shlomi Cohen; Muriel Webb; Anat Yerushalmy-Feler; Achiya Amir; Dana L. Gal; Ronit Lubetzky (BMC, 2021)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) can range from simple steatosis to steatohepatitis with or without fibrosis. The predictors for liver fibrosis and the effect of nutritional intervention on hepatic fibrosis in pediatric population are not well established. We aimed to investigate the predictors for liver fibrosis and the effects of short-term nutritional intervention on steatosis and fibrosis among obese adolescents with NAFLD. Methods Cross-sectional study among obese adolescents. Sociodemographic and clinical data were collected. Liver fibrosis was estimated by Shearwave elastography. All participants were recommended to consume a low carbohydrate diet and were followed biweekly. Blood tests and elastography were performed upon admission and repeated after 3 months. Results Fifty-seven pediatric patients were recruited (35 males, mean age 13.5±2.9 years, mean body mass index [BMI] 38.8±9.7). Liver fibrosis was diagnosed in 34 (60%) subjects, which was moderate/severe (F≥2) in 24 (70%). A higher BMI Z score and moderate/severe steatosis correlated with moderate/severe fibrosis (P < 0.05). Seventeen patients completed 3 months of follow-up and displayed a decrease in BMI Z score (from BMI Z score 2.6±0.5 before intervention to 2.4±0.5 after intervention), with a significant decrease in liver fibrosis (P = 0.001). Conclusion Pediatric patients with high BMIs and severe liver steatosis are at risk for severe liver fibrosis. Nutritional intervention with minimal weight loss may improves hepatic fibrosis among the pediatric population. Trial registration TRN NCT04561804 (9/17/2020)